Pengaruh Booklet Terhadap Pengetahuan Pasien Hipertensi di Puskesmas Rasimah Ahmad Kota Bukittinggi: The Influence Booklet on Knowledge of Hypertension Patient at Rasimah Ahmad Health Center Bukittinggi City - Rizqa Hasanah; Yelly Oktavia Sari; Fatma Sri Wahyuni; Miming Andika (JURNAL FARMASI DAN MAKANAN, 2023)
Hypertension is a chronic disease that requires long-term therapy. The prevalence of hypertension continues to increase every year, but patient knowledge of treatment is still low. Better knowledge will increase patient compliance in treatment so that blood pressure is better controlled and the risk of complications is avoided. This study aims to determine the effect of booklets on the knowledge of hypertensive prolanis patients at the Rasimah Ahmad Health Center, Bukittinggi City. The type of research used was an experimental pretest – posttest control group design with 40 respondents who were randomly divided into two groups (control and intervention). The intervention medium used in this study was a booklet. The instrument used was the HK-LS questionnaire to assess knowledge. The results of the study showed an increase in the compliance of hypertensive patients. The statistical analysis used was the Wilcoxon Signed Ranks test, to determine the effect of the intervention on the patient's level of knowledge. From the results of the study, it showed that giving booklets obtained a significant value (p-value = 0.000), so it could be concluded that giving booklets had an effect on increasing the knowledge of hypertensive prolanis patients at the Rasimah Ahmad Health Center, Bukittinggi City.